The muscle protein synthetic response to meal ingestion following resistance-type exercise - Trommelen, J.; Betz, M. W.; van Loon, L. J. C. (Sports Medicine, 2019)
Protein ingestion following resistance-type exercise stimulates muscle protein synthesis rates and consequently enhances the skeletal muscle adaptive response to prolonged training. Ingestion of?~?20 g of quickly digestible protein isolate optimizes muscle protein synthesis rates during the first few hours of post-exercise recovery. However, the majority of daily protein intake is consumed as slower digestible, nutrient-rich, whole-food protein sources as part of mixed meals. Therefore, the muscle protein synthetic response to the ingestion of protein supplements and typical foods or mixed meals may differ substantially. In addition, the muscle protein synthetic response to feeding is not only determined by acute nutrient intake but is also likely modulated by habitual energy and nutrient intake and nondietary factors such as habitual physical activity, body composition, age, and/or sex. Therefore, nutritional recommendations to maximize the muscle protein synthetic response to exercise depend on the type of meal (e.g., protein supplements vs. mixed meals) and the time until the next feeding opportunity (e.g., feeding before overnight sleep) and, therefore, need to be personalized to the individual athlete.